(untitled) (Journal of Parents and Teachers, 2026)
It addresses the "functional interview" at school, which is used to make decisions, resolve conflicts, or coordinate tasks. It highlights the importance of timing, atmosphere, active listening, and keeping the conversation on track. It presents various strategies for communicating and evaluating ideas and attitudes, showing how to plan and conduct successful interviews.